Evaluation of serum hepcidin as a biochemical marker in diagnosis of anemia of chronic disease - Vyas, Sonal; Suman, Sanjeev; Kapoor, Anil; Nema, S. K. (International Journal of Research in Medical Sciences, 2018)
Background: Anemia is a serious public health problem. It affects two billion people worldwide, particularly infants and young children mainly in developing countries where its etiology is multifactorial. Anemia in infancy is generally associated with impaired cognitive and behavioral development, impaired oxygen transport and a poorer prognosis in the context of many chronic diseases or chronic infections. The Present study aims to detect the serum hepcidin and ferritin levels in chronic disease anemia and correlate the values of serum hepcidin levels with their serum ferritin levels and IL-6 levels. Methods: A total of 86 individuals were enrolled in the study. Sample for hematological evaluations were collected and estimation was carried out for biomarker estimation by ELISA method(s) using specified kit(s) procured commercially. The statistical evaluation was done using SPSS version 24.0. Analysis of variance (ANOVA) and Pearson's correlation tests were used to compare the variables and to see the correlation between the different variables. Results: In present study, we observed statistically significant lower values of RBC count, Hbgm/dl, MCV, MCH, MCHC in ACD group than the normal group. For serum hepcidin when ROC curves and Pearson’s scattered plot were made in case of ACD group; the ROC was recorded to be maximum >0.869; with a sensitivity of 84.62% and specificity 94.12% while the confidence level was 95% with an interval of 0.779 to 0.932. Further, the cutoff point determined was >72.93. Thus, the hepcidin level > 72ng/mL and above is related to the ACD. These cut off points had strong confidence interval and valuable predictive potential. Conclusions: Serum Hepcidin can be used as a simple and cost effective diagnostic marker for identification of anemia.